2010
DOI: 10.4314/ajbr.v10i2.50614
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fasting Plasma Glucose and Glycated Haemoglobin In Adult Diabetic Nigerians

Abstract: The relationship between packed cell volume (PCV), fasting plasma glucose (FPG) and glycated haemoglobin (HbA I ) was investigated in 40 diabetic patients (22 males and 18 females) and 20 apparently healthy controls (12 males and 18 females). Among the control subjects the FPG and HbA1 were significantly higher in the female than male subjects (P < 0.001). This gender differences was not found in diabetic patients (P < 0.05). While all the control subjects have FPG and HbA1 level within normal range (75-115m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Additionally, in this investigation, FBS had positive correlation with PT and APTT, though not statistically significant and considerably positive association with PCV (p<0.05) while it showed negative correlation with platelet. The correlation between FBS and PCV is in agreement with the study by Akinloye et al (30) who also showed a positive correlation between fasting plasma glucose (FPG) and PCV, while it is in disagreement with Nnenna et al (31) who observed significant correlation between PT and APTT. This finding adds to the evidence that hyperglycemia plays a role in the development of prothrombotic alterations, as shown in clamp experiments (32).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Additionally, in this investigation, FBS had positive correlation with PT and APTT, though not statistically significant and considerably positive association with PCV (p<0.05) while it showed negative correlation with platelet. The correlation between FBS and PCV is in agreement with the study by Akinloye et al (30) who also showed a positive correlation between fasting plasma glucose (FPG) and PCV, while it is in disagreement with Nnenna et al (31) who observed significant correlation between PT and APTT. This finding adds to the evidence that hyperglycemia plays a role in the development of prothrombotic alterations, as shown in clamp experiments (32).…”
Section: Discussionsupporting
confidence: 85%
“…The study was carried out at the Federal Medical Centre (FMC), Owo, which is a tertiary medical facility in Nigeria. A total of 100 subjects consisting of forty (40) gestational diabetic subjects (GDM), thirty (30) age nongestational diabetes pregnant women (NGPW) attending the ante-natal clinic of the hospital and thirty (30) women with neither diabetes nor pregnancy (NDNP) were enrolled as controls in this study.…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
“…These differences were statistically significant (P<0.001) and consistent with the reports given by Verma M et al [10] and Akinloye OA et al [11] The PPBS levels in both the study groups were significantly high when compared to control. This finding is consistent with the findings of Fahmy E et al [12] HbA1c was increased in diabetic compared to control, and further increase in HbA1c was observed in diabetic patients with complication when compared to control, which is a sign of poor glycemic status as described by Selvin E et al [13]and Nakamura K et al [14] In diabetic patients, concentration of HbA1c is elevated as much as two fold (Gabbay KH et al) [15] and decreases with improvement of glycemic control.…”
Section: Discussionsupporting
confidence: 81%
“…4 HbA 1C expressed as a percentage of total blood hemoglobin concentration gives a good retrospective assessment of the mean plasma glucose concentration during the preceding 6-8 weeks while the recent glycemic level has the highest influence and the preceding 30 days contribute only upto 50%. [5][6][7] A cut-off value of 6.5% HbA 1C classifies diabetic subjects with a specificity of 98.7%. 8 Normal level of HbA 1C is 4-5.9%.…”
Section: Introductionmentioning
confidence: 99%